Analysis of Torsional Vibration Mechanics and Sensitivity for Planar Sinusoidal Steel Ball Transmission Mechanism - Ning Linfei; Zhang Si; Li Meiqiu; Luo Jingbo; Shi Yinghua (Jixie chuandong)
With the wide application of planar sinusoidal ball movable teeth transmission in various industries，the study of its dynamic characteristics and vibration problems is also very important. Aiming at the torsional vibration model and its inherent characteristics of planar sinusoidal ball transmission mechanism，a 5-DOF torsional vibration mechanical model is established by using the lumped parameter method. Based on the undamped free vibration equation，the natural frequency and modal modes of the system are calculated. The sensitivity of the natural frequency of the system to the inertia and stiffness parameters is analyzed by the partial derivative method，and the structural parameters which have significant influence on the natural frequencies of the system are concluded. In order to avoid resonance between the system and the external excitation，the parameters with high sensitivity to the natural frequency of the system are modified to improve the operation stability of the system.